Government Health Communication on Instagram: Stunting Prevention in West Java Province - Muhammad Zakky Fauzur Rahman (Universitas Islam Darul Ulum Lamongan, 2026)
Stunting remains a critical public health issue in Indonesia, making government communication key in translating health policies into public awareness and preventive actions. While many public institutions extensively use social media, little research has examined how provincial government agencies strategically leverage Instagram to address long-term health concerns such as stunting prevention. This study explores the digital communication approach of the West Java Province's National Population and Family Planning Board via their Instagram account @bkkbnjawabarat. It adopts a qualitative case study methodology, including in-depth interviews, Instagram documentation, and visual observation. Guided by Stuart Hall’s representation theory and Ostergaard’s 3A campaign effect model—awareness, attitude, and action—the findings reveal that Instagram serves as a vital communication tool due to its visual appeal and wide reach. Nonetheless, the campaign has yet to realize its full potential; educational messages are often overshadowed by ceremonial institutional content, local cultural references are underutilized, emotional engagement remains limited, and action-focused content lacks clear behavioral instructions. The study argues that digital government communication should be evaluated not only by platform activity but also by its capacity to deliver meaningful, culturally relevant, and behaviorally impactful messages.